Study on Designing and Quality Aspects of Aseptic Process Simulation - S. Hemanth Kumar; Teja Sri Maddirala; T. Shailesh; M. P. Gowrav; D. V. Gowda (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
Aseptic process simulation is a crucial validation technique carried out before a new product, or aseptic process is introduced in the facility and also to prove at regular intervals that the existing manufacturing operations are carried out in a state of aseptic conditions. This review addresses the nature of the study involved in aseptic process simulation, speed and number of runs, runtime, the atmospheric conditions, line speed, the media used, incubating & analysing media-filled units, data interpretation. It also focuses on worst-case parameters, interventions, case study on interventions and the regulatory aspects concerned with the simulation. Aseptic process simulation involves conducting aseptic production using a sterile growth medium instead of actual drug solution and excipients. The processes involved in aseptic process validation include identifying process mechanisms, variables, and control methods, including product, component, sterilisation of equipment, sanitary facilities, environmental checks, and staff training on gowning procedures.